The TorRS two component system regulates expression of TMAO reductase in response to high hydrostatic pressure in Vibrio fluvialis - Liu, Na; Jiang, Ting; Cui, Wen-Peng; Qi, Xiao-Qing; Li, Xue-Gong; Lu, Yuan; Wu, Long-Fei; Zhang, Wei-Jia (Frontiers in Microbiology, 2023)
High hydrostatic pressure (HHP) regulated gene expression is one of the most commonly adopted strategies for microbial adaptation to the deep-sea environments. Previously we showed that the pressure induced trimethylamine N-oxide (TMAO) reductase improves the pressure tolerance of deepsea strain Vibrio fluvialis QY27. Here, we investigated the molecular mechanism of HHP-dependent regulation of TMAO reductase TorA. By constructing torR and torS deletion mutants, we demonstrated that the two-component regulator TorR and sensor TorS are responsible for the HHP-responsive regulation of torA. Unlike known HHP-responsive regulatory system, the abundance of torR and torS was not affected by HHP. Complementation of the ΔtorS mutant with TorS altered at conserved phosphorylation sites revealed that the three sites were indispensable for substrate-induced regulation, but only the histidine located in the alternative transmitter domain was involved in pressure-responsive regulation. Taken together, we demonstrated that the induction of TMAO reductase by HHP is mediated through the TorRS system and proposed a bifurcation of signal transduction in pressureresponsive regulation from the substrate-induction. This work provides novel knowledge of the pressure regulated gene expression and will promote the understanding of the microbial adaptation to the deep-sea HHP environment.